“ANALYSIS OF TOTAL PHYSICAL RESPONSE METHOD APPLIED IN TEACHING VOCABULARY AT 3RD YEAR OF BASIC EDUCATION “A” AT UNIDAD EDUCATIVA “JOSÉ MARÍA ROMÁN” IN RIOBAMBA CITY, CHIMBORAZO PROVINCE, DURING THE ACADEMIC YEAR 2018-2019” - Pazmiño Montachana, Myrian Beatriz (2019)
Using suitable methods facilitate the English teaching-learning process. In addition, it helps to develop the four language skills and the acquisition of vocabulary so that students can communicate. However, nowadays traditional methods and techniques are still used in the classroom to teach vocabulary. Therefore, the student’ learning objectives may not be meaningful. In this regard, the objective is to analyze how Total Physical Response method helps to learn new vocabulary at 3rd year basic education at Unidad Educativa “José María Román”, in the city of Riobamba, Chimborazo province, during the academic year 2018-2019. This study was proposed since along the observation practices, it was evident that there were some difficulties in learning vocabulary and to assimilate language easily. The observed population consisted of 30 students. The study type was qualitative. The research level was exploratory, it was used the ethnographic method. The observation was used as technique and the instrument to collect the data was through a checklist bearing in mind the theoretical basis presented in the theoretical framework. The analysis and interpretation of results was developed according to the specific objectives. Finally, it was concluded that the application of the TPR method was not correct due to some steps are omitted, for this reason it was not possible to achieve a meaningful learning.